THE MEDIATING ROLE OF JOB SATISFACTION IN THE RELATIONSHIP BETWEEN WORK ENVIRONMENT, COMPENSATION, AND EMPLOYEE PERFORMANCE - Ramadhan Yanti; Usman Usman (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study examines the mediating role of job satisfaction in the relationship between work environment, compensation, and employee performance at PT Bank Pembangunan Daerah Sulawesi Tenggara (Bank Sultra) Wakatobi Branch. A quantitative explanatory research design was employed using census sampling involving 40 employees. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings reveal that work environment and compensation have positive and significant effects on both job satisfaction and employee performance. Job satisfaction also has a positive effect on employee performance and partially mediates the relationships between work environment, compensation, and employee performance. These findings indicate that improving employee performance requires a supportive work environment, fair compensation practices, and enhanced job satisfaction. This study contributes empirical evidence to the human resource management literature, particularly regarding the mediating role of job satisfaction in the regional banking sector.